Special and differential treatment in CARICOM (ECLAC [Port of Spain]TT, 2007)
Provides an analysis and assessment of special and differential treatment in Caricom. Describes and analyzes the provisions for it, establishes its purpose and examines how it has been rendered operational in practice. Establishes its effect and implications on sectors, firms, products receiving it. Makes policy recommendations.
Keywords: TRADE PREFERENCES